Synthesis, Spectroscopic Characterization And Antimicrobial Evaluation of Novel Nitrogen Containing Metal Complexes - El-Boraey, Hanaa A.; El-domiaty, Aballah (JOURNAL OF ADVANCES IN CHEMISTRY, 2019)
Four novel Mn(II), Co(II), Cu(II) complexes with nitrogen containing ligand (L) i.e. N,N-((Z)-ethane-1,2-diylidine)bis(2-amino benzo hydrazide) have been synthesized and structurally characterized by elemental analysis, spectral, thermal (TG/DTG), molar conductance and magnetic susceptibility measurements. From the spectroscopic and magnetic studies it has been concluded that all complexes have a six coordinated octahedral geometry. The Schiff base and their metal complexes have also been screened for their antibacterial and antifungal activities by using a modified Kirby-Bauer disc diffusion method.